Casticin, a flavonoid isolated from Vitex rotundifolia, inhibits prolactin release in vivo and in vitro - Ye Qi; Zhang Qiao-yan; Zheng Cheng-jian; Wang Yang; Qin Lu-ping (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the anti-hyperprolactinemia activity of casticin, a flavonoid isolated from Vitex rotundifolia, and elucidate its molecular mechanism. Methods: Hyperprolactinemia (MIHP) was induced by administration of metoclopramide dihydrochloride (50 mg/kg, tid, ip, for 10 d) in SD rats and the primary pituitary cells were prepared from the pituitary glands of the SD rats. Prolactin concentrations were measured using a radioimmunoassay. Cell viability was measured using an MTT assay. The mRNA expression of estrogen receptor alpha and beta in rat pituitary cells was measured using semi-quantitative RT-PCR analysis. Results: The level of serum prolactin in the MIHP model group was 2.1 fold higher than that in the untreated control group (P